Efeitos de resfriamento artificial e tempo de armazenamento sobre a qualidade tecnológica e fisiológica de grãos de trigo - Silva, Kelly Pelc da (2017)
Wheat is among the staple foods in the world, beingconsumed on all continents. In order to meet the annual consumption demand, the harvested wheat must be stored until the next harvest. In storage the grains face adverse conditions such as microbiological contamination, insect pests and breakdown by metabolism. For the maintenance of the technological and physiological quality, the use of low temperatures is presented as a technique for the storage management of wheat grains. This work aimed to evaluate the quality of wheat stored in an artificially cooled environment by determining the technological and physiological characteristics of the grains. The work was carriedout with the use of natural environment treatments with insecticide, cooled environment andcooled environment with diatomaceous earth. The evaluated variables were the impact caused by the technical breakdown, quantitative losses, qualitative losses, changes in the physical, chemical and rheological characteristics of the flour. The results were analyzed using the statistical analysis and, in the significant models, the means compared to each other by the Tukey test 95% confidence interval. During storage time, changes were observed in stored grains, with reduction in fungal counts, accelerated aging, moisture, proteins, lipids, falling number, mixture tolerance index, tenacity and relation between tenacity and extensibility. In determinations of vigor and fat acidity of the grains stored in natural environment, artificially cooled wheat, water absorption, stability, extensibility and gluten strength occurred elevations of values. With the storage time the values of PH, thousand grain mass, ashes and gluten did not vary significantly (p> 0.05). Artificial cooling is effective in preserving the physiological quality and technology of stored wheat grains. Artificial cooling is a viable technique in storage of wheat, with indication of diatomaceous earth use to prevent possible losses due to insectplague attack.